Kelimpahan Serangga Arboreal Pada Padi Sawah Di Kelurahan Lempake Kota Samarinda Kalimantan Timur - Hidayatullah, Achmad Rivaldy; Hariani, Nova; Trimurti, Sus (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The study of arboreal insect abundance in paddy field in Lempake village, Samarinda, Kalimantan Timur province has been conducted in June until December 2017. The purpose of this study is to know the kinds of arboreal insects in paddy field in Lempake Village. Sampling are using sweeping net and Light trap. The data obtained is displayed in the form of description. During the research, Arboreal insects obtained in 3 phases rice paddy field growth (from the vegetative to the harvesting phases in the rice field) in Lempake were 33 genera classified in 8 orders, namely Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, Mantodea, Odonata, Orthoptera. In the vegetative phase of paddy were found 20 genera, generative phase 16 genera and pre-harvest phase 17 genera.